Dynamic material flow and stock analysis of residential buildings by integrating rural–urban land transition: A case of Shanghai. (20th April 2020) - Gao, Xiaofeng; Nakatani, Jun; Zhang, Qian; Huang, Beijia; Wang, Tao; Moriguchi, Yuichi
Abstract: In rapidly developing countries, such as China, considerable quantities of construction materials have been mobilized with the fast expansion of urban areas. The rural to urban land use transition, especially the upgrade and redevelopment of original rural areas, is a noted driver of material flows. This rural–urban land transition should be incorporated into material flow and stock analyses to provide a more accurate analysis. In this study, a dynamic material flow and stock model that integrates the historical rural–urban land transition was developed to explore the quantity of material stocks and demolition waste from residential buildings in Shanghai—the largest megacity in China from 1950 to 2100. Our results show that the material stocks from residential buildings in Shanghai increased 41-fold from 1950 to 2010, about 957 MMT (million metric tons), and is estimated to be saturated around 2040. Material stocks have experienced asynchronized growth in rural areas, central urban areas, and rural–urban land transition zones (RULT zones) in Shanghai. Until 2040, the RULT zones in Shanghai will be the largest material repository (62%), followed by central urban areas (20%), and rural areas (18%). The amount of demolition waste, which accounted for 10 MMT in 2010, is expected to peak at 29 MMT in 2060s. This suggests the need for a deliberate investment plan to increase waste treatment capacity. In addition, the dominant component of demolition waste will shift from brick to concrete after 2020s. The RULT zones will contribute two-thirds of demolition waste to Shanghai until the 2060s. If we do not consider the reality of the physical status of buildings in RULT zones, the demolition waste will be underestimated by the maximum of 57% in 2003 in urban areas. The key findings on the trend of construction and demolition (C&D) waste generation and the significant contribution of RULT zones can be used as a reference for the strategic planning of treatment facilities. This research framework can be also used to estimate the amount of C&D waste in other fast-developing cities in China and other countries. Graphical abstract: UR buildings = urban residential buildings; RR buildings = rural residential buildings. RULT zones = rural–urban land transition zones. Image 1 Highlights: A dynamic material flows and stocks model by integrating rural–urban land transition was applied in Shanghai, China. Material stocks & demolition waste in rural areas, RULT zones, and central urban areas were considered, respectively. Two-thirds of demolition waste will generate from rural–urban land transition zones by 2060s. Dominant component of demolition waste will shift from brick to concrete. Prolonging the buildings' lifetime would be a priority option for waste reduction.